Designing a working drawing of the welcome gate for Batuah Tourism Village, Kutai Kartanegara - Putra, Hatta Musthafa Adham; Hakim, Bhanu Rizfa (Community Empowerment, 2021)
This Community Service (PkM) aims to increase the attractiveness of the Batuah Tourism Village, Kutai Kertanegara Regency through designing of the welcome gate. Batuah Tourism Village is a leading village in Kutai Kartanegara Regency, East Kalimantan Province which has Elai fruit as a tourism commodity. To improve the tourist attraction, the gate design is made with the shape of an elai fruit as the main icon. The gate of the Batuah tourist village is located on the Balikpapan - Samarinda axis road, so the design is expected to be attractive and informative. This community service was carried out through discussion with the Head of Batuah Village in order to get an overview of the form and vision to be conveyed. Besides, the community service team made a gate design and presented it to the community of Batuah Village. The official designs that have been approved submitted to the Kutai Kartanegara Regency Government.